The Influence of Therapeutic Group Therapy on Improving Adolescent Self-Concept in Flood Refugees, Sei Rampah District, Serdang Bedagai Regency, North Sumatra in 2021 - Syahferi (Science Midwifery, 2022)
Self-concept as a whole includes the abilities they have, the feelings they experience, their physical condition and their immediate environment. Negative self-concepts are triggered by a number of things, ranging from an inability to respect oneself to an inability to carry out roles within the family and surrounding friends. using a pre-experimental type with a one group pretest and posttest design. The total research population is all adolescents who have a negative self-concept. Sampling was carried out using the Non Probability technique,Non-Probability Samplingis a sampling technique that does not provide equal opportunities or opportunities for each element or member of the population to be selected as a sample, resulting in 16 respondents who have a negative self-concept. Data analysis used the Paired T Test. The results of the study using the Paired T Test obtained a p value of 0.000 (p <0.05). This shows that there is an effect of Therapeutic Group Therapy on Improving Adolescent Self-Concept in Flood Refugees, Sei Rampah District, Serdang Bedagai District, North Sumatra in 2021. The conclusion is that there is an effect of therapeutic group therapy on increasing Adolescent Self-Concept in Flood Evacuations, Sei Rampah District, Serdang Bedagai District, North Sumatra Year 2021.